2023
DOI: 10.3390/microorganisms11030741
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Endometrial Microbiome in Patients with Recurrent Implantation Failure

Abstract: An abnormal endometrial microbiota has been associated with implantation failure; therefore, it may be important to evaluate it in order to improve reproductive outcomes in infertile patients. The main objective of our study was to compare the endometrial microbiome of patients with recurrent implantation failure (RIF) and control patients undergoing assisted reproduction treatment (ART). A prospective cohort study including forty-five patients with their own or donated gametes. The endometrial microbiome was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…In a prospective cohort study by Koedooder et al, a cohort of 303 women were subject to pre-IVF vaginal sampling, revealing that individuals harboring an unfavorable vaginal microbiota composition exhibited a sevenfold lower likelihood of achieving pregnancy compared to those with a favorable profile [ 18 ]. Consistent findings indicated that infertile women, particularly those encountering recurrent implantation failure (RIF), exhibited decreased Lactobacillus growth and heightened Gardnerella growth, distinguishing them from their fertile controls [ 20 , 22 , 23 ]. Gardnerella species are linked to chronic inflammation and altered immune responses in the vaginal environment.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective cohort study by Koedooder et al, a cohort of 303 women were subject to pre-IVF vaginal sampling, revealing that individuals harboring an unfavorable vaginal microbiota composition exhibited a sevenfold lower likelihood of achieving pregnancy compared to those with a favorable profile [ 18 ]. Consistent findings indicated that infertile women, particularly those encountering recurrent implantation failure (RIF), exhibited decreased Lactobacillus growth and heightened Gardnerella growth, distinguishing them from their fertile controls [ 20 , 22 , 23 ]. Gardnerella species are linked to chronic inflammation and altered immune responses in the vaginal environment.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial infection and inflammation can lead to aberrant local immune responses in the endometrium and consequently prevent embryo implantation ( Wang et al, 2022 ). Furthermore, the dysregulation of endometrial microbiota has been associated with implantation failure ( Lozano et al, 2023 ). Endometrial receptivity refers to the ability of the endometrium to allow the localization, adhesion, penetration, and implantation of blastocysts, as well as to enable embryo implantation and development ( Lessey & Young, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this study showed the superiority of the vaginal swab over the endometrial sample as a biomarker for repeated implantation failure. The prospective cohort study by Lozano et al also compared the endometrial microbiome of a group of patients diagnosed with RIF with that of a control group without RIF [ 15 ]. Here, in contrast to the study by Ichiyama et al, a significantly lower rate of lactobacilli was found in the patients with RIF.…”
Section: Discussionmentioning
confidence: 99%